Intrapartum factors associated with neonatal hypoxic ischemic encephalopathy: a case-controlled study - Vanessa E. Torbenson; Mary Catherine Tolcher; Kate M. Nesbitt; Christopher E. Colby; Sherif A. EL-Nashar; Bobbie S. Gostout; Amy L. Weaver; Michaela E. Mc Gree; Abimbola O. Famuyide (BMC, 2017)
Abstract Background Neonatal encephalopathy (NE) affects 2-4/1000 live births with outcomes ranging from negligible neurological deficits to severe neuromuscular dysfunction, cerebral palsy and death. Hypoxic ischemic encephalopathy (HIE) is the sub cohort of NE that appears to be driven by intrapartum events. Our objective was to identify antepartum and intrapartum factors associated with the development of neonatal HIE. Methods Hospital databases were searched using relevant diagnosis codes to identify infants with neonatal encephalopathy. Cases were infants with encephalopathy and evidence of intrapartum hypoxia. For each hypoxic ischemic encephalopathy case, four controls were randomly selected from all deliveries that occurred within 6 months of the case. Results Twenty-six cases met criteria for hypoxic ischemic encephalopathy between 2002 and 2014. In multivariate analysis, meconium-stained amniotic fluid (aOR 12.4, 95% CI 2.1-144.8, p = 0.002), prolonged second stage of labor (aOR 9.5, 95% CI 1.0-135.3, p = 0.042), and the occurrence of a sentinel or acute event (aOR 74.9, 95% CI 11.9-infinity, p < 0.001) were significantly associated with hypoxic ischemic encephalopathy. The presence of a category 3 fetal heart rate tracing in any of the four 15-min segments during the hour prior to delivery (28.0% versus 4.0%, p = 0.002) was more common among hypoxic ischemic encephalopathy cases. Conclusion Prolonged second stage of labor and the presence of meconium-stained amniotic fluid are risk factors for the development of HIE. Close scrutiny should be paid to labors that develop these features especially in the presence of an abnormal fetal heart tracing. Acute events also account for a substantial number of HIE cases and health systems should develop programs that can optimize the response to these emergencies.